2011
DOI: 10.1590/s0074-02762011000800017
|View full text |Cite
|
Sign up to set email alerts
|

The genetic diversity and phenotypic characterisation of Streptococcus agalactiae isolates from Rio de Janeiro, Brazil

Abstract: Streptococcus agalactiae isolates are more common among pregnant women, neonates and nonpregnant adults with underlying diseases compared to other demographic groups. In this study, we evaluate the genetic and phenotypic diversity in S. agalactiae strains from Rio de Janeiro (RJ) that were isolated from asymptomatic carriers. We analysed these S. agalactiae strains using pulsed-field gel electrophoresis (PFGE), serotyping and antimicrobial susceptibility testing, as well as by determining the macrolide resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 29 publications
1
30
0
Order By: Relevance
“…Erythromycin resistance has been documented worldwide in studies concerning S. agalactiae strains of human and bovine origin. In the United States and Europe, resistance rates of approximately 4-50% have been reported (DIPERSIO; DIPERSIO, 2006;DOGAN et al, 2005;GUÉRIN-FAUBLÉE et al, 2002;SADOWY et al, 2010), while in Brazil, estimates have been lower than 10% (CORRÊA et al, 2011;DUARTE et al, 2004DUARTE et al, , 2005PALMEIRO et al, 2010). However, of the Brazilian bovine isolates examined by Pinto et al (2013), 27.6% were resistant to this antibiotic, a higher value than that recorded in the present work (19.5%).…”
Section: Resultsmentioning
confidence: 99%
“…Erythromycin resistance has been documented worldwide in studies concerning S. agalactiae strains of human and bovine origin. In the United States and Europe, resistance rates of approximately 4-50% have been reported (DIPERSIO; DIPERSIO, 2006;DOGAN et al, 2005;GUÉRIN-FAUBLÉE et al, 2002;SADOWY et al, 2010), while in Brazil, estimates have been lower than 10% (CORRÊA et al, 2011;DUARTE et al, 2004DUARTE et al, , 2005PALMEIRO et al, 2010). However, of the Brazilian bovine isolates examined by Pinto et al (2013), 27.6% were resistant to this antibiotic, a higher value than that recorded in the present work (19.5%).…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, serotype does not seem to have a correlation with the classification of a GBS isolate in a clonal group. Relationships between the serotype and the source of isolation or between the serotypes and PFGE profiles were also not detected in another Brazilian study [14]. This fact could be explained by the occurrence of capsule switching between GBS isolates by horizontal gene transfer, as a result of pressures by immune response of the host [7].…”
Section: Discussionmentioning
confidence: 96%
“…Other studies have described the predominance of serotypes III and V among cases of infection in neonates and in non-pregnant adults, respectively [25,34] while serotype Ia was found to predominate among GBS causing invasive infections in non-pregnant adults in Portugal [36]. In Brazil, previous studies showed that serotypes Ia, II, III and V were found in 68.2% of isolates predominantly from vaginal specimens of asymptomatic pregnant woman [14]. On the other hand, serotype IV was detected in 13.1% of the isolates from Curitiba city, Paraná state, Brazil, being most of them from infectious cases [13], and serotypes Ib (34.9%) and Ia (25.6%) were predominant among a cohort of HIV-infected pregnant women in Rio de Janeiro city [35].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is a close relationship between serologic type and virulence in these microorganisms. 9,15,[20][21][22] In our study, multiplex PCR identified the serotypes Ia, V, II, Ib, III, VI. Serotype VI is rarely described: it had never been reported in Brazil or in other Latin American countries until this day.…”
Section: ■ Discussionmentioning
confidence: 87%